Characterization of the silicon isotopic composition of the terrestrial biogenic output from a boreal forest in Northern Sweden - Engström, Emma; Rodushkin, Ilya; Baxter, Douglas; Ingri, Johan; Öhlander, Björn (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2007)
During the last decade, the potential plant impact on the biogeochemical cycle of Si via the large terrestrial biogenic Si reservoir formed by vegetation has attracted considerable interest. It has been concluded that the release of silicic acid from dissolution of soil phytoliths might exceed the Si mobilized by weathering of Si-containing primary minerals, which implies that the biogenic contribution to the total content of Si in the soil profile must be considered in weathering studies. Information about Si isotopes can potentially be used for differentiation between relative contributions from biogenic and mineral sources in natural waters, soil solutions and plants. This would, however, require thorough characterization of the terrestrial biogenic Si reservoir, a task that received somewhat limited attention to date. The aim of the present study was to characterize the Si isotopic composition of a boreal forest, with bedrock consisting of dolomitic limestone, in Northern Sweden. Representative biomass from the forest area exhibited a surprisingly homogenous Si isotopic composition, ranging from δ29Si (-0.14 ± 0.05)‰ (2σ) to (0.13 ± 0.04)‰. Further, a change in the Si isotopic composition of (+0.39 ± 0.04)‰ has been detected in Leymus arenarius, indicating predominant accumulation of heavier isotopes from spring to autumn. Recent studies of Si isotopic composition in plants have been focused on the root uptake of dissolved silicic acid as the only Si accumulation path. Results acquired during the present study provide compelling evidence to suggest that exogenous Si is also incorporated in the surface structure of the plant material. A surface contribution in excess of 5% of the total Si would introduce a significant shift in the bulk isotopic composition (>0.1‰) assuming that the exogenous material differed by 2‰ from the biogenic Si. This strongly suggests that the surface contribution must be carefully considered during in situ uptake studies. Godkänd; 2007; 20110704 (andbra)